Dampak Environmental dan Social Disclosure terhadap Profitabilitas Perusahaan Batu Bara - Ayu Kartika; Nurul Khotimah; Rini Dwiastutiningsih (Jurnal Aplikasi Perpajakan, 2025)
This study aims to determine and analyze the effect of environmental disclosure and social disclosure on the profitability of companies in the coal sub-sector of the energy sector listed on the Indonesia Stock Exchange. The research method used is a quantitative descriptive method with literature and documentation research methods. The data used is secondary data obtained from the annual reports of companies in the coal sub-sector of the energy sector listed on the Indonesia Stock Exchange for the period 2019-2023. The analytical tools used in this study consist of classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests. Based on the results of the study, it shows that the application of Environmental Disclosure has a partial effect on Company Profitability. Meanwhile, Social Disclosure has no partial effect on Company Profitability. However, simultaneously, Environmental Disclosure and Social Disclosure have an effect on Company Profitability.